Exploring the fraud triangle model and microeconomic factors in zakat embezzlement - Muhammad Irwan Ariffin; Tengku Dania Madhihah Tengku Mahadi; Suraya Pakair; Dayang Fatin Fatihah Zolkefle (Journal of Islamic Accounting and Finance Research, 2025)
Purpose - This study aims to explore the factors contributing to zakat embezzlement, using the fraud triangle theory and a microeconomic perspective to better understand the underlying dynamics in zakat mismanagement. Method - This study employs a qualitative research methodology, combining a review of relevant literature on the fraud triangle theory and its application to zakat management with thematic content analysis of interviews conducted with two experts in financial corruption and zakat management. The literature review examines academic and industry sources to explore drivers of zakat embezzlement, including opportunities, pressures, and rationalizations. Interviews with a financial management researcher and a zakat management official provide firsthand insights, which complement the desk-based research and contribute to a comprehensive understanding of the issue. Result - The study reveals that financial pressure, weak internal controls, and rationalization drive zakat embezzlement. The lack of transparency and governance in zakat institutions provides opportunities for mismanagement, while personal financial gain and ethical rationalization further exacerbate the issue. Implication - These findings suggest the need for stronger governance, better internal controls, and ethical training in zakat institutions. Strengthening transparency and accountability could reduce opportunities for embezzlement, thereby enhancing the effectiveness of zakat as a tool for poverty alleviation. Originality - This research uniquely applies the fraud triangle framework to zakat embezzlement, integrating microeconomic elements such as utility maximization and information asymmetry.